Avaliação de coeficientes aerodinâmicos de pressão em telhados quatro águas - Pol, William de Oliveira (2022)
Every building is subject to wind action consistent with its immersion zone, that is, depending on the surrounding conditions and its geometry will be the magnitude of the force imposed on it. The external pressure, important for developing structural projects, is essentially dependent on the flow turbulence properties and, above all, on the velocity. They are the external pressure coefficients that relate the force acting on the solid immersed to the flow, with the dynamic force of the wind to the windward side of the building, which is bound to the roughness, wind incidence and shape of the building. Therefore, through the pressure coefficients it is determined how much of the dynamic pressure of the wind will be taken as effort in the structural analysis. The hip roofs began to be studied after post-hurricane analyzes revealed that some less damaged or intact homes had this type of coverage. Henceforth, this typology became known for its proven resistance to extreme winds, being commonly used in civil construction. In Brazil, the ABNT NBR 6123:1988 standard, which recommends the calculation of actions due to wind in buildings, does not include a hipped roof in its premises. Therefore, the objective is, from computational fluid dynamics (CFD) simulations, evaluating different geometric proportions and slopes of different roofs, it is possible to map the wind behavior to determine calculation subsidies for its adequate sizing. To this end, essays from consolidated studies were reproduced in order to validate the numerical methodology and, on the other hand, compare it with codes ASCE-7:2022, National Building Code of Canada 2005, EUROCODE-1991-1- 4:2010 and AS/NZS 1170.2 .2011:2017 holders of great international reputation. At the end of the process, an initial contribution of an abacus of external pressure coefficients for hip roofs is proposed to assist structural engineers in the determination of wind actions with this roof typology.